2013
DOI: 10.4161/gmic.27290
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 and carbon monoxide regulate intestinal homeostasis and mucosal immune responses to the enteric microbiota

Abstract: Heme oxygenase-1 (HO-1) and its enzymatic by-product carbon monoxide (CO) have emerged as important regulators of acute and chronic inflammation. Mechanisms underlying their anti-inflammatory effects are only partially understood. In this addendum, we summarize current understanding of the role of the HO-1/ CO pathway in regulation of intestinal inflammation with a focus on innate immune function. In particular, we highlight our recent findings that HO-1 and CO ameliorate intestinal inflammation through promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 46 publications
2
42
0
1
Order By: Relevance
“…Similarly to above mentioned observations, CORM-3 significantly reduced intestinal inflammation and oxidative stress in postoperative ileus due to activation of p38 MAPK and downregulation of ERK1/2 [48]. Taken together, it can be assumed that CO has immunomodulatory properties and affects the activity of various cell types including T cells, B cells, epithelial cells, neutrophils, mast cells, dendritic cells and macrophages stimulated in the course of gastrointestinal digestive disorders [49]. Takagi et al investigated the effects of CO-releasing CORM-A1 on Th17 differentiation using T-cell transfer-induced colitis in mice [50].…”
Section: Co Physiology and Pharmacologysupporting
confidence: 69%
See 1 more Smart Citation
“…Similarly to above mentioned observations, CORM-3 significantly reduced intestinal inflammation and oxidative stress in postoperative ileus due to activation of p38 MAPK and downregulation of ERK1/2 [48]. Taken together, it can be assumed that CO has immunomodulatory properties and affects the activity of various cell types including T cells, B cells, epithelial cells, neutrophils, mast cells, dendritic cells and macrophages stimulated in the course of gastrointestinal digestive disorders [49]. Takagi et al investigated the effects of CO-releasing CORM-A1 on Th17 differentiation using T-cell transfer-induced colitis in mice [50].…”
Section: Co Physiology and Pharmacologysupporting
confidence: 69%
“…They revealed that CORM-A1 ameliorated intestinal inflammation through reduction of retinoid related orphan receptor (ROR)γ-receptor expression, inhibition of Th17 differentiation and by the decrease of IL-17A level [50]. HMOX-1/CO pathway can also regulate intestinal inflammation in acute and chronic experimental models by cross-talk of this pathway proteins with enteric microbiota in mucosal immune compartment [49]. Undoubtedly, CO could be considered as potential therapeutic agent in various GI disorders due to the wide range of molecular inflammatory and anti-inflammatory targets affected by this small gaseous molecule.…”
Section: Co Physiology and Pharmacologymentioning
confidence: 99%
“…Moreover, cytoprotective molecules that are under the transcriptional control of NRF2 in eukaryotes can also be produced by commensal bacteria. For instance, the HO-1 homologs in the microbiota may greatly contribute to GI homeostasis, and this can be therapeutically exploited for local delivery of carbon monoxide to the intestine (Onyiah et al, 2014).…”
Section: Nuclear Factor (Erythroid-derived 2)-like 2 In the Digestmentioning
confidence: 99%
“…For example, HO-1 deficiency not only results in inadequate pathogen clearance (14) but also promotes the development of necrotizing enterocolitis-like intestinal injury in mice (15). HO-1 and HO-1-induced carbon monoxide can ameliorate intestinal inflammation through promotion of bacterial clearance (16). The HO-1/carbon monoxide pathway also suppresses Toll-like receptor 4 (TLR4) signaling, leading to downregulation of proinflammatory signaling induced by stimulation with LPS (17).…”
mentioning
confidence: 99%